CARA PEMUTAKHIRAN NILAI EKIVALEN MOBIL PENUMPANG DAN KAPASITAS DASAR RUAS JALAN LUAR KOTA - Hikmat Iskandar (Jurnal Jalan-Jembatan, 2010)
Passenger car equivalent (pce) converts unit of traffic flow from vehicles per hour to passenger car unit (pcu). A traffic flow consists of several types of vehicles such as passenger car, bus,truck, and motor cycle are converted to a uniform unit of traffic flow, ie. pcu, by assuming that a vehicle other than passenger car is 'replaced' by a passenger car multipled by pce. Each type of vehicle has its owned pce value and different from other, depending on influences of it's presence in a trafic flow. Basic capacity is a maximum number of vehicle that may be reached under a specified standard geometric condition and by an undisturb traffic condition. Pce is used to convert unit of a basic capacity from vehicles/hour to pcu/hour. This paper aimed to discus methods of defining pce and basic capaity of inter urban roads, including data required for testing capacity of inter urban roads, including data required for testing applicabiliy of the method. The review showed that for inter urban road segment, pce may be derived from a relationship between speeds versus flow rate of each individual type of vehicles, whereas the basic capacity may be derived from a linear relationship between densities versus speeds. Application of the method to a set of traffic flow data showed that the method may be used for defining values of emp and basic capacity. The results of analyzing a segment of Nagreg-Tasikmalaya data showed that emp and basic capacity tend to change. Key words : Inter-urban roads, road capacity, speed-density relationship, pce, pcu